2019
DOI: 10.1186/s12885-019-6027-0
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic tumor in type 1 autoimmune pancreatitis: a diagnostic challenge

Abstract: Background The co-occurrence of type 1 autoimmune pancreatitis (AIP) and pancreatic tumor (PaT) has been previously reported. Pure AIP cases have favorable prognosis and are primarily treated with steroids, while AIP cases with PaT are associated with poor prognosis where the primary management is pancreatic resection. However, it’s a challenge to timely identify the concurrent PaT in AIP because of their similar clinical and radiological manifestations. Methods We retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
(63 reference statements)
0
9
0
Order By: Relevance
“…Comments: Diagnosis of AIP is not always straightforward and, in some cases, it is not easy to differentiate it from pancreatic cancer. Furthermore, an incidence of concomitant pancreatic tumours (benign and malign) in patients with AIP has been reported in up to 7% of cases 47 . The International Study Group of Pancreatic Surgery consensus statement reported that 5–13% of patients undergoing surgical resections because of suspected malignancy had benign findings on pathology, with AIP accounting for 30–43% of these findings 48 .…”
Section: Introduction and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Comments: Diagnosis of AIP is not always straightforward and, in some cases, it is not easy to differentiate it from pancreatic cancer. Furthermore, an incidence of concomitant pancreatic tumours (benign and malign) in patients with AIP has been reported in up to 7% of cases 47 . The International Study Group of Pancreatic Surgery consensus statement reported that 5–13% of patients undergoing surgical resections because of suspected malignancy had benign findings on pathology, with AIP accounting for 30–43% of these findings 48 .…”
Section: Introduction and Methodologymentioning
confidence: 99%
“…Furthermore, an incidence of concomitant pancreatic tumours (benign and malign) in patients with AIP has been reported in up to 7% of cases. 47 The International Study Group of Pancreatic Surgery consensus statement reported that 5-13% of patients undergoing surgical resections because of suspected malignancy had benign findings on pathology, with AIP accounting for 30-43% of these findings. 48 In a retrospective study, including pathological analysis of 274 patients who underwent pancreaticoduodenectomy because of presumed malignancy, the prevalence of benign disease was 8.4%, and overall prevalence of AIP was 2.6%.…”
Section: Q22: What Are the Imaging Features Of Aip? Statement 22mentioning
confidence: 99%
“…Different clinical and radiological modalities, including serum IgG4, CA19‐9, tumour‐specific antigens, gene expression, endoscopic ultrasonography, computerised tomography (CT) and magnetic resonance imaging (MRI), have been explored for differentiating AIP from pancreatic cancer. Radiological studies can be suggestive, but not diagnostic 5,21,22 . Serum IgG4 levels above twice the upper limit of normal are often seen in type 1 AIP, but the sensitivity is not perfect 23–26 .…”
Section: Discussionmentioning
confidence: 99%
“…It's in no doubt that focal pancreatic enlargement, low density on CT, female gender, and rim enhancement on MRI in patients with AIP type 1 are suggestive of pancreatic cancer in these patients (18).…”
Section: Autoimmune Pancreatitis and Pancreatic Cancermentioning
confidence: 98%
“…Ikeura et al(17), also in his review article, summarizes the incidence risk of pancreatic cancer in AIP patients at between 0 % and 4.8%. Pancreatic cancer occurs in the vast majority of people with type 1 AIP(8,18).AIP is a clinical manifestation of a group of diseases called IgG4-RD. In this context, the question arose whether IgG4-RD were associated with the induction of the process of carcinogenesis.…”
mentioning
confidence: 99%